GE_GERICHTE C/7808/2017 vom 15. November 2017 - GE Cour de justice (2017)
DROIT D'AUTEUR ET DROITS VOISINS ; TARIF(EN GÉNÉRAL) ; COPIE ; COMPENSATION DE CRÉANCES ; DÉPENS ; VALEUR LITIGIEUSE | LDA.59.3; CO.120.1;